Modelling marine particle dynamics with LTRANS-Zlev: implementation and validation. (March 2020) - Laurent, Célia; Querin, Stefano; Solidoro, Cosimo; Canu, Donata Melaku
Abstract: This paper presents the release of LTRANS-Zlev, which is a new version of the off-line Lagrangian ocean particle-tracking model LTRANS v.2b that is compatible with a Z-coordinate (constant-depth layers) discretization of the hydrodynamic equations. The model capitalizes on and massively extends the capabilities of the original code LTRANS, which is already quite popular, but can be used only adopting a sigma-coordinate (terrain-following layers) discretization. Among the additional features included in LTRANS-Zlev, there are the backward-in-time particle-tracking algorithm and some new customizable larval behaviour options. The new version also includes the OILTRANS-module for oil spill simulations. The new implementations were validated by using the output of the Z-coordinate Massachusetts Institute of Technology general circulation model (MITgcm) for an idealized case study describing a cyclonic gyre in a mid-latitude closed basin. Another test-case, in which larval dispersal is modelled in the northern Adriatic Sea, illustrates some of the new features of LTRANS-Zlev. Graphical abstract: Image 1 Highlights: We describe the off-line Lagrangian ocean particle-tracking model LTRANS-Zlev. Compatible with both Z (depth) and sigma (terrain following) vertical coordinate systems. Several larval behaviours can be customized by the user. Oil weathering processes can be handled with the OILTRANS module.